Effects of Polypropylene and Date Palm Fiber Reinforcements on High Performance Concrete at Elevated Temperatures and Their Impact on Spalling Phenomena - Malek Hamda; Cherif Guergah; Abdelaziz Benmarce; Abderrahmane Khechekhouche; Antonio Marcos de Oliveira Siqueira; Júlio Cesar Costa Campos (The Journal of Engineering and Exact Sciences)
Concrete, a widely utilized construction material, faces challenges related to thermal instability when exposed to fire-induced temperature variations. To address the issue of explosive spalling, common concerns in concrete, polypropylene fibers, recommended by Eurocode 2, are added to the mix. This study aimed to evaluate alterations in physical and mechanical properties of high-performance concrete incorporating various fibers, including polypropylene and palm tree waste as an eco-friendly alternative to conventional fibers. The incorporation of palm fibers aligns with the promotion of local materials for their potential affordability due to local abundance. The assessment involved four high-performance concrete formulations tested under high-temperature conditions: SF (silica fume without fibers), SFPP (silica fume with polypropylene fibers), SFDF (date palm fibers with silica fume), and SFPPQS (polypropylene fibers with quarry sand, siliceous sand, and silica fume). Destructive and non-destructive evaluations encompassed compressive strength, flexural strength, ultrasonic pulse velocity, and mass loss. Experimental tests were conducted at room temperature (20°C) and elevated temperatures (250°C, 450°C, and 650°C). Results revealed a decline in both compressive and flexural strength for samples exposed to temperatures above 450°C. Notably, the inclusion of date palm fibers mitigated mass losses while exhibiting a lower compressive strength.